2022
DOI: 10.1002/hipo.23411
|View full text |Cite
|
Sign up to set email alerts
|

Temporal pole volume is associated with episodic autobiographical memory in healthy older adults

Abstract: Recollection of personal past events differs across the lifespan. Older individuals recall fewer episodic details and convey more semantic information than young. Here we examine how gray matter volumes in temporal lobe regions integral to episodic and semantic memory (hippocampus and temporal poles, respectively) are related to age differences in autobiographical recollection. Gray matter volumes were obtained in healthy young (n = 158) and old (n = 105) adults. The temporal pole was demarcated and hippocampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 109 publications
1
20
0
Order By: Relevance
“…As was the case in experiment 1, the benefit of replay on recall of internal details was observed in every participant. This pattern of results was also obtained after adjusting for verbal output ( SI Appendix , section 2.5 and Table S5 ) ( 42 , 43 ). Moreover, replay benefitted all subtypes of Internal details (Internal Event, Time, Place, Perceptual, and Thought/Emotion; SI Appendix , section 2.3, Fig.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…As was the case in experiment 1, the benefit of replay on recall of internal details was observed in every participant. This pattern of results was also obtained after adjusting for verbal output ( SI Appendix , section 2.5 and Table S5 ) ( 42 , 43 ). Moreover, replay benefitted all subtypes of Internal details (Internal Event, Time, Place, Perceptual, and Thought/Emotion; SI Appendix , section 2.3, Fig.…”
Section: Resultssupporting
confidence: 62%
“…Although the overall number of internal details declined over time, the relative benefit of cued reactivation was preserved: replayed events were recalled with 58.9% more event-specific details than baseline events at delayed testing. This pattern of results was also obtained after adjusting for verbal output by dividing detail count by word count on a trial-by-trial basis ( SI Appendix , section 2.5 and Table S5 ) ( 42 , 43 ). Moreover, repeated HippoCamera replay benefitted all subtypes of internal detail (internal event, time, place, perceptual, and thought/emotion; SI Appendix , section 2.3, Fig.…”
Section: Resultsmentioning
confidence: 52%
“…The study of trait-level AM has fostered a deeper understanding of how AM and non-mnemonic cognition interact. It has also moved the field toward uncovering how individual variation in brain structure and function shape the way in which humans recall the personal past, at scales ranging from the biophysical properties of axons (Clark et al, 2022) resting-state functional connectivity (Setton et al, 2022a), and temporal lobe volumetry (Setton et al, 2022b). However, several open questions remain, such as the appropriate factor structure for the AI and how it covaries with other related domains such as perception, language, and attention.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic information for this sample is shown in Table 1. We have recently reported on a subset of these participants with neuroimaging data (Setton et al, 2022a; Setton et al, 2022b).…”
Section: Methodsmentioning
confidence: 99%
“…The medial temporal lobe subsystem of the default network, which incorporates the hippocampus and many of its cortical and subcortical connections (including the parahippocampal cortex, retrosplenial cortex, the posterior cingulate cortex, and the inferior parietal lobe), may have an essential role in the sort of cognitive demands required of retrieving and (re)binding vivid, contextualized elements of past events, future events, and atemporal scenes, possibly working collaboratively with the medial prefrontal cortex (Andrews-Hanna & Grilli, 2021; Gaesser et al, 2013; Romero et al, 2019; Sheldon et al, 2019; Summerfield et al, 2010). In fact, recent neuroimaging research using the same Autobiographical Interview scoring approach as the present study has found that individual differences in structural and functional measures of parts of the default network medial temporal lobe subsystem significantly relate to episodic (internal) detail remembering among cognitively normal older adults (Matijevic et al, 2022; Memel et al, 2020; also Setton et al, 2022, in a sex specific pattern).…”
Section: Discussionmentioning
confidence: 55%